Religious Behaviour of Mosque Congregation during the Covid-19 Pandemic with a Neuroscience Perspective: A Case Study at the Jogokariyan Mosque Yogyakarta - Jailani, Mohammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The spread of Covid-19 during Ramadan 1442 H led to the closure of all worship activities in most places. However, the Jogokariyan Mosque in Yogyakarta maintained active religious activities attended by its congregation. This study aims to analyze the vertical religious behavior between God and human beings, specifically among the congregation of Jogokariyan Mosque during the COVID-19 pandemic. This research adopts a qualitative method with a case study approach. The informants include 20 mosque congregants, 1 mosque takmir, and 2 Ramadan 1442 H committee members. Data collection techniques encompass interviews, observations, and documentation, while data analysis involves reduction, data display, and conclusion drawing/verification methods. The findings reveal that the congregation's religious behavior during Ramadan was well-organized and followed the activities scheduled by the mosque takmir. These activities included breaking fast events, tarawih prayers, and religious studies conducted both online and offline. The mosque congregation enthusiastically participated in these events with seriousness and dedication. The study demonstrates that these behaviors align with psychosocial and neurospiritual theories, highlighting the resilience and spiritual commitment of the community amidst the pandemic. This research contributes to the understanding of vertical religious behavior during crises, enriching psychosocial and neurospiritual perspectives within the context of Islamic spirituality. Future research can explore broader contexts or comparative studies across different religious communities to deepen insights into the dynamics of religiosity during challenging